Improving The Students’ Ability On Listening Using Whisper Race Game At Mts Al Washliyah Batang Serangan - Nazli Fahada; Saidatul Hanim; Jonris Tampubolon (English Lecturers and Teachers Association (ELTA), 2023)
The aims of this research are to find out the effectiveness of whisper race games strategy in improving the students' ability on listening. This research is a classroom action research. The action research was conducted in two cycles, each of which involved planning, implementing, observing and reflecting. The subject of this research was the first year students of MTS Al-Washliyah Batang Serangan. The subject of this research was 37 students in class VII. The technique of collecting data were interview, document, observation and test. After analyzing the data, it was found out that the students' score increased from pretest until post test of cycle I and cycle II. It means there is an improvement on the students ability on listening through whisper race game strategy. It was shown from the improvement of the means of students' score namely the mean of post test of cycle I (66.75) was higher than the mean of the students' score in pretest (46.75) and the mean of cycle II (79.45) was higher than the mean of the students’ score in post test I. It can be seen that the score continuously improved from the pre-test until the post test of cycle 2. And for the presentation in post test I 29.73% was higher than pre test 5.40% and the post test II 62.16% it was higher than pre test and post test 1. From the hypothesis data computation that t-count =9.27 and t-table df-N-1= 37-1=36. It can be seen that coefficient of t-count = 9.27 with the fact level a = 0.05 which the real level of t –table =2,02 in the coefficient of t-count (9.27)>t-count = (2.02). Thus, the hypothesis is acceptable. Based on the finding the statistics analysis stating that Whisper Race Game strategy can improve the students ability on listening Keywords : whisper race game , listening